Metaracism: explaining the persistence of racial inequality - Wilson, Carter A. (Lynne Rienner Publishers, 2015)
What is metaracism? -- The structure of metaracism -- The culture of metaracism -- Politics, the state, and the maintenance of racial oppression -- The growth of inequality -- The assault on social welfare and education policies -- The incarceration crisis -- Minority vote suppression -- Metaracism at a crossroads